A comparative study of Korean and Chinese learners’ strategy use in request-refusal continuous dialogue speech acts - Liang Xu; Xiao Wu (PLoS ONE, 2026)
In daily communications, the use of speech acts that may threaten others’ faces, such as request and refusal, is inevitable. By methods of DCT with 24 coherent request-refusal scenarios as well as optimized classification of request and refusal strategies, differences in request-refusal continuous dialogue speech acts between Native Korean (NK) and Chinese Korean language learners of intermediate level (CKLI) and advanced level (CKLA) were examined. There were statistically significant differences in frequencies of NK, CKLA, and CKLI using request and refusal strategies in different scenarios. Overall, NK used more categories and numbers of strategies than CKLI. The gap between NK and CKLI might narrow as language proficiency increases. Furthermore, not only the single influence factor that affected strategy choice but also the interactions between these factors, suggesting that people might behave differently when faced with complex scenarios consisting of multiple factors. This study also proposes a new research methodology that inserts factors affecting strategy choice into individual scenarios, designs multiple independent scenarios with the same factors, and analyses the effects of these factors and their interactions on strategy choice. The results of the associated analysis could be used to assist in the development of a detailed instructional plan.